Caracterización de pacientes atendidos en el posgrado de periodoncia de la UAN en el periodo comprendido del 2016 al 2021 (2022)
Periodontal disease is chronic multifactorial and inflammatory, which is associated with the biofilm of bacteria in the oral cavity, its main feature is its progressive destruction, affects the alveolar bone and tissues adjacent to the tooth, periodontitis is present in most adults and begins in young people.